The Moral Aspect based on the Concept of Human Development in the Travelogues Pelukis Jalanan and Arkitek Jalanan by Teme Abdullah: (Aspek Akhlak Berdasarkan Konsep Pembangunan Insan dalam Travelog Pelukis Jalanan dan Arkitek Jalanan Karya Teme Abdullah) (Malay Literature, 2021)
The Takmilah theory is a theory of Islamic literature that is familiar in the academic sphere, especially in the field of literature in Malaysia. It emerged from an awareness among literary scholars to highlight Islamic literature to the public. However, most existing studies only use philosophical literary works as the main reference for analysis and critique, and highlight modern literary genres, such as the travelogue, as mere literary works. Therefore, this study highlights contemporary literary works in the form of travelogues in London entitled Pelukis Jalanan and Arkitek Jalanan as the main sources to unravel the concept of Takmilah theory as a theory of Islamic literature. Next, this study also incorporates the background of the architect and author who is well known for his mysterious identity, Teme Abdullah. This study utilizes the sixth principle of the Takmilah theory, which is the Principle of Perfecting the Self, in order to relate it to the concept of human development from a moral aspect. Through this study, it can be determined that there is a major aspect that can be associated with achievement in the concept of human development by an individual or a writer, which is the aspect of continuous moral improvement so as to achieve perfection in life. Evidently, this analyzed aspect is directly related to the Principle of Perfecting the Self, as outlined in the Takmilah theory. Therefore, it can be concluded that the contemporary works of Teme Abdullah should be characterized as works of Islamic literature because they comply with admirable values that are in line with Islamic principles.